Intermediate filaments: Integration of cell mechanical properties during migration - Infante, Elvira; Etienne-Manneville, Sandrine (Frontiers in Cell and Developmental Biology, 2022)
Cell migration is a vital and dynamic process required for the development of multicellular organisms and for immune system responses, tissue renewal and wound healing in adults. It also contributes to a variety of human diseases such as cancers, autoimmune diseases, chronic inflammation and fibrosis. The cytoskeleton, which includes actin microfilaments, microtubules, and intermediate filaments (IFs), is responsible for the maintenance of animal cell shape and structural integrity. Each cytoskeletal network contributes its unique properties to dynamic cell behaviour, such as cell polarization, membrane protrusion, cell adhesion and contraction. Hence, cell migration requires the dynamic orchestration of all cytoskeleton components. Among these, IFs have emerged as a molecular scaffold with unique mechanical features and a key player in the cell resilience to mechanical stresses during migration through complex 3D environment. Moreover, accumulating evidence illustrates the participation of IFs in signalling cascades and cytoskeletal crosstalk. Teaming up with actin and microtubules, IFs contribute to the active generation of forces required for cell adhesion and mesenchymal migration and invasion. Here we summarize and discuss how IFs integrate mechanical properties and signalling functions to control cell migration in a wide spectrum of physiological and pathological situations.